Perceptions of wildlife in rehabilitation from images and statements - Buckanoff, Halley; Williams, Kai (Frontiers in Human Dynamics, 2024)
People form perceptions of the approachability of wild animals from images and statements involving non-domestic animals under human care. Exactly what these perceptions are has previously been studied in primates. A survey using constructed images and statements about wild animals in care was circulated via email and social media to stakeholders in wildlife rehabilitation. Respondents were asked to categorize each statement or image as representing a pet, education animal, or a releasable wild animal. The results, such as 94% of respondents choosing wild animal when presented with a best practice image supported our hypothesis that best practice images and technical names provoked perceptions that the animals were releasable wild animals. Contrary to our hypothesis that not-recommended practices and anthropomorphic labels would lead to perceptions of the animals as pets, we instead found that these scenarios produced an ambiguous grouping of responses among the categories, as in the case where when presented with an ambiguous image 48% labeled it as a pet and 42% labeled it as a wild animal. Practitioners of wildlife rehabilitation should always use clear technical language and best practice images in public communications to appropriately portray the animals as wild denizens temporarily in care.